Maternally derived chemical defenses are an effective deterrent against some predators of poison frog tadpoles (Oophaga pumilio) - Stynoski, Jennifer Lynn (2014)
Parents defend their young in many ways, including provisioning chemical defences. Recent work in a poison frog system offers the first example of an animal that provisions its young with alkaloids after hatching or birth rather than before. But it is not yet known whether maternally derived alkaloids are an effective defence against offspring predators. We identified the predators of Oophaga pumilio tadpoles and conducted laboratory and field choice tests to determine whether predators are deterred by alkaloids in tadpoles. We found that snakes, spiders and beetle larvae are common predators of O. pumilio tadpoles. Snakes were not deterred by alkaloids in tadpoles. However, spiders were less likely to consume mother-fed O. pumilio tadpoles than either alkaloid-free tadpoles of the red-eyed treefrog, Agalychnis callidryas, or alkaloid-free O. pumilio tadpoles that had been hand-fed with A. callidryas eggs. Thus, maternally derived alkaloids reduce the risk of predation for tadpoles, but only against some predators.